The Advantage of Incumbents in Coalitional Bargaining - Meriläinen Jaakko; Tukiainen Janne (United States, 2022)
Political parties frequently form coalitions with each other to pursue office or policy payoffs. Contrary to a prominent argument, the distribution of rents within the coalition does not always reflect the relative sizes of the coalition members. We propose that this is at least partially due to an incumbency advantage in coalitional bargaining. To evaluate this argument empirically, we construct a data set of candidates, parties, and members of the executive in Finnish local governments. We first use a regression discontinuity design to document a personal incumbency advantage in nominations to executive municipal boards. We then show that an incumbency premium is present also at the party level. Using an instrumental variable strategy that hinges on within-party close elections between incumbents and non-incumbents, we find that, ceteris paribus, having more re-elected incumbents increases party’s seat share in the executive.